2010
DOI: 10.21608/eajbsa.2010.15250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the climate and some different protein diets on the visitation pattern of flesh and blow flies of Gebel Al- Baher, Al- Baha Province, Kingdom Saudi Arabia

Abstract: This work compares the effect of the climate and some different protein diets on the activity of flesh and blow fly populations in one of the biggest mountains of Sarah region, southwest Kingdom of Saudi Arabia. Trapping of adult flies revealed the presence of three populations, namely, Engelisca adhamae (Lehrer & AbouZied, 2008) and Liosarcophaga babiyari (Lehrer, 1995), in addition to a single calliphorid species Calliphora vicina (R−D, 1830). Adults of L. babiyari showed a year round activity, with the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…At present, the majority of studies on C. pinguis have been focused on its external morphology [10,18,19], submicroscopic structure [20][21][22], karyotypes [23], geographical abundance [24][25][26][27], myasis [28] and DNA-based techniques used for species identification [17,29,30]. However, there have not been any developmental studies of this species [31].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the majority of studies on C. pinguis have been focused on its external morphology [10,18,19], submicroscopic structure [20][21][22], karyotypes [23], geographical abundance [24][25][26][27], myasis [28] and DNA-based techniques used for species identification [17,29,30]. However, there have not been any developmental studies of this species [31].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Saudi Arabia, it was found that fish bait was preferred by two of the three fly species collected (Abouzied 2010). Furthermore, Yepes-Gaurisas et al (2013) reported that using fish to attract Sarcophagidae is highly effective.…”
Section: Discussionmentioning
confidence: 99%